Persepsi Remaja Putus Sekolah Terhadap Pola Asuh Orang Tua - Bonaventura R. seto Se; Karolus Charlaes Bego (Jayapangus Press, 2021)
The purpose of this study is to know: Why teenagers choose to drop out. What are the perceptions of adolescents about parental parenting patterns. This type of research is qualitative research. This research was carried out because in wuring village area still found many teenagers who dropped out of school and are still in school age. Teenagers drop out of high school for deviant behavior. The results found that the main factor causing the subject or adolescent dropout in Wuring Village was a family factor. The family background is broken home like a parental divorce. The pattern of parenting applied to their children uses permissive parenting patterns and authoritarian fostering patterns compared to democratic fostering patterns.